METAFORA INDRAJĀLA KONSEP INTERKONEKTIVITAS SEMESTA DALAM VEDA - Ni Putu Widyastuti (Veda Jyotih: Jurnal Agama dan Sains, 2022)
Indrajāla is the concept of universal holographic interrelationship which relates to energy, consciousness and continuity of universal multidimensional processes. This concept is related to Vedic Cosmology which denies separateness in the universe. This article describes the concept of Indrajāla in the Vedas which later became the central doctrine in Buddhism. This concept has great implications for the consciousness of mankind that everything is connected energetically through a net of illusions that are invisible, but have a real impact. This article was written based on literature research using Sri Aurobindo's Vedic interpretation. The results of this study indicate that the concept of Indrajāla has manifested in various forms and has become the main teaching in Mahayana Buddhism and subsequently reformulated into the concept of universal unity and interconnectedness. A complex interconnection network formed by the relationships between objects in a system, including social networks, particle interactions, and symbols representing ideas in the brain or intelligent computer system. The concept of a universal hologram is directly related to cosmic consciousness and the connectivity of energy in the universe. The implications of this concept will be able to build public awareness that one thought or event will have a wide impact, interrelatedness and interdependence between elements in the universe, including humans and the cosmos.